COMPARATIVE ANALYSIS OF TOTAL FACTOR PRODUCTIVITY AMONG POTATO (Solanum tuberasum) FARMERS IN BOKKOS LOCAL GOVERNMENT AREA OF PLATEAU STATE, NIGERIA - Folorunso, Solomon; Bayo, D. (FUDMA JOURNAL OF SCIENCES, 2020)
This study compared Total Factor Productivity among potato farmers in Bokkos Local Government Area of Plateau State, Nigeria. A multistage sampling technique was employed to select 96 male and 64 female respondents. Data was collected from primary source through the distribution of structured questionnaire and oral interview schedule. Data collected were analyzed using descriptive statistics, net farm income and total factor productivity (TFP) models. The findings revealed that the mean age of male and female household heads was 40 and 38 years respectively, the mean household size was 5 persons for male and 4 persons for female headed households, 82.3% and 73.5 of male and female respondents were married. The mean farming experience of male and female farmers was 19 and 15years, 62% and 66% of male and female respondents did not belong to any cooperative. Potato production was profitable with NFI per hectare of male and female respondents being N473,307.65 and N294,324.45 respectively. The BCR was 3.15 and 5.16 for male and female respondents. Profitability Index was 0.68 and 0.81 respectively for male and female farmers. The result of probit regression revealed that the coefficients of gender, household size, farming experience and amount of credit were significant. The study recommend that: implicit sensitization of the community leaders on the active role of women in agricultural development, Policy makers at all level of government should ensure discriminatory laws or customs against women are abolished, both male and female farmers should utilize more of their household members in